Specific heat of CeIn3-xSnx single crystals in the vicinity of the quantum critical point - Rus, T.; Wilhelm, H.; Stockert, O.; Luhmann, T.; Caroca-Canales, N.; Sereni, J.G.; Geibel, C.; Steglich, F.; Sereni, Julián (Elsevier, 2005)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina